Tetrakis(acetoxymercuri)methane: a polymetallic reagent for labeling sulfur in nucleic acids. - Strothkamp, K G (1978)
Tetrakis(acetoxymercuri)methane binds to the sulfur atom of 6-thioguanosine and also to the 4-thiouridine residue of Escherichia coli tRNAVal. A 4:1 complex is formed between 6-thioguanosine and tetrakis(acetyoxymercuri)methane. Addition of 3 equivalents of N,N-dimethyl-2-amino-ethanethiol hydrochloride to tetrakis(acetoxymercuri)methane effectively blocks three of the four mercury atoms, rendering the compound monofunctional toward 6-thioguanosine. Under appropriate conditions, tetrakis(acetyoxymercuri)methane, in the presence or absence of N,N-dimethyl-2-amino-ethanethiol hydrochloride, binds to the 4-thiouridine residue in E. coli tRNAVal without forming intermolecular crosslinks. These results suggest that tetrakis(acetoxymercuri)methane will be a useful polymetallic reagent for labeling sulfur sites in polynucleotides. It may also prove to be a valuable reagent for preparing heavy metal derivatives of proteins for x-ray crystallographic study.